2016
DOI: 10.1371/journal.pone.0166391
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Risk Stratification Model for ST-Elevation Myocardial Infarction (STEMI) from the Combination of Blood Examination Variables: Acute Myocardial Infarction-Kyoto Multi-Center Risk Study Group

Abstract: BackgroundMany mortality risk scoring tools exist among patients with ST-elevation Myocardial Infarction (STEMI). A risk stratification model that evaluates STEMI prognosis more simply and rapidly is preferred in clinical practice.Methods and FindingsWe developed a simple stratification model for blood examination by using the STEMI data of AMI-Kyoto registry in the derivation set (n = 1,060) and assessed its utility for mortality prediction in the validation set (n = 521). We selected five variables that sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Generally speaking, the more key variates a model includes, the more precisely it predicts. The newly developed laboratory stratification model [21] is also used to judge STEMI acute outcomes. The Global Registry of Acute Coronary Events score includes several retrospective factors [22], and the Thrombolysis In Myocardial Infarction (TIMI) risk index is defined by age, systolic blood pressure, and heart rate [23].…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the more key variates a model includes, the more precisely it predicts. The newly developed laboratory stratification model [21] is also used to judge STEMI acute outcomes. The Global Registry of Acute Coronary Events score includes several retrospective factors [22], and the Thrombolysis In Myocardial Infarction (TIMI) risk index is defined by age, systolic blood pressure, and heart rate [23].…”
Section: Discussionmentioning
confidence: 99%
“…[24] Risk stratification and prognosis prediction are critical in identifying high risk patients and decision making for the treatment of patients with AMI. [5] Conventional risk scoring systems including the thrombolysis in myocardial infarction (TIMI), the global registry of acute coronary events (GRACE), and the acute coronary treatment and intervention outcomes network (ACTION) scores are widely validated and accepted tools that are estimated using patients’ clinical information. [68] However, these prognostic models have limitations for the current daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have reported on the combined use of laboratory-only parameters in risk models for in-hospital mortality in patients with ACS, including STEMI [29][30][31][32][33]. Compared with models that use novel biomarkers, such as copeptin and suppression of tumorigenicity 2 [31,32], our model should be easy to perform in the actual clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with models that use novel biomarkers, such as copeptin and suppression of tumorigenicity 2 [31,32], our model should be easy to perform in the actual clinical setting. Yanishi et al [33] also reported a simple risk stratification model that was based on the combined use of laboratory parameters to predict in-hospital mortality in Japanese patients with STEMI. In that study, the authors found that a risk-weighted combination model containing the 5 following variables: WBC count and levels of hemoglobin, CRP, creatinine, and BS, could predict that risk.…”
Section: Discussionmentioning
confidence: 99%